1992
DOI: 10.1111/j.1439-0507.1992.tb00886.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of a Candida albicans sepsis with a combination of flucytosine and fluconazole

Abstract: Zusammenfassung. Es wird eine schwere Verlaufsform einer Candida‐albicans‐Sepsis vorgestellt, die erfolgreich mit der Kombinationstherapie Flucytosin plus Fluconazol behandelt wurde. Nach einem großen bauchchirurgischen Eingriff entwickelte ein 70‐jähriger Patient eine fulminante Candida‐albicans‐Sepsis mit beginnendem Nierenversagen. Letzteres zwang uns, eine therapeutische Alternative zum “Gold‐Standard” Amphotericin B plus Flucytosin zu suchen. Summary. A case of a severe Candida sepsis is reported, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In this regard, combination of two or more drugs has been suggested and tested for C. albicans and other Candida species and found to be synergistic for amphotericin B/ketoconazole, 5-FC/ketoconazole, and other combinations as well [151, 152]. The drug combination therapy was also tested in mice model and patients [153, 154]. In a recent study, Tavanti et al have shown that clinical isolates of C. glabrata (low susceptibility to azole drugs) are susceptible to human cationic peptide hepcidin (Hep-20) (100–200  μ g/mL).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, combination of two or more drugs has been suggested and tested for C. albicans and other Candida species and found to be synergistic for amphotericin B/ketoconazole, 5-FC/ketoconazole, and other combinations as well [151, 152]. The drug combination therapy was also tested in mice model and patients [153, 154]. In a recent study, Tavanti et al have shown that clinical isolates of C. glabrata (low susceptibility to azole drugs) are susceptible to human cationic peptide hepcidin (Hep-20) (100–200  μ g/mL).…”
Section: Discussionmentioning
confidence: 99%
“…We chose the combination of FLCZ and 5-FC as the initial antifungal therapy in the present case based on the antifungal activity against both Cr. neoformans and C. albicans infection (44,45). On the other hand, if a non-albicans Candida species e.g., C. glabrata or C. krusei, had been identified, these antifungal agents would have been changed to LFAmB.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of antifungals flucytosine (5FC) and amphotericin B (AMB) is recommended by the Infectious Diseases Society of America for Candida infections ( Pappas et al, 2015 ) due to the high rate of resistance developed during 5FC monotherapy ( Barchiesi et al, 2000 ). Other combinations between two antifungals have been put through clinical trials ( Scheven et al, 1992 ; Ghannoum & Elewski, 1999 ; Rex et al, 2003 ; Pachl et al, 2006 ), but so far only the 5FC + AMB combination therapy has a clinical role ( Pappas et al, 2015 ). Common combinations studied are between a commercial antifungal and a specific inhibitor of a protein of interest; for example, antifungals combined with Hsp90 inhibitors ( Cowen, 2013 ; Veri & Cowen, 2014 ) or protein kinase C inhibitors ( LaFayette et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%